Haploinsufficiency of ABL1 is associated with dominant isolated omphalocele - Kolvenbach, Caroline; Yilmaz, Öznur; Lopes, Filipa M.; Kalanithy, Jeshurun C.; Lemberg, Katharina; Sharma, Vineeta; Majmundar, Amar J.; Geyer, Matthias; Woolf, Adrian S.; Hildebrandt, Friedhelm; Odermatt, Benjamin; Reutter, Heiko (Frontiers in cell and developmental biology, 2025)
Omphalocele is a rare birth defect of the abdominal wall that results in herniation of the visceral organs through the umbilicus. To date, there are no identified genetic causes for non-syndromic isolated omphalocele. Exome sequencing in a four-generation multiplex family with isolated dominant omphalocele revealed a novel extended splice site variant (c.310 + 3A>C; p.?) in ABL1 that encoded a non-receptor tyrosine kinase. Consistent with in silico predictions, in peripheral blood, this variant leads to an alternatively spliced mRNA harboring a premature termination codon. Quantification of the ABL1 mRNA abundance showed its significant reduction in an affected allele carrier compared to a healthy control. These data indicate degradation of the aberrantly spliced transcript by non-sense-mediated decay (NMD), consistent with haploinsufficiency as the disease mechanism. Accordingly, exposure to different tyrosine kinase inhibitors during pregnancy is associated with a significantly higher risk of omphalocele in the exposed offspring. ABL1 is a causative gene for congenital heart defect and skeletal malformation syndrome (CHDSKM) and human ABL1 deficiency syndrome (HADS); CHDSKM is associated with gain-of-function while HADS is associated with 3′ truncating variants, likely escaping NMD. Therefore, allele-dependent mechanisms may explain the phenotypic diversity. In human embryos (45-47 days post fertilization), ABL1 was immunodetected in fibroblast-like cells in the umbilical cord as well as abdominal wall surface ectoderm, both of which are important sites for abdominal wall closure. In mouse embryos (embryonic days 14.5-15.5), wholemount in situ hybridization confirmed Abl1 expression in the umbilical cord. Our genetic and experimental findings provide evidence that ABL1 haploinsufficiency is the first monogenic cause for isolated dominant omphalocele.